The social construction of the value of wildlife: A green cultural criminological perspective - Uhm, Daan P. van (Theoretical criminology, 2018)
The trade in wildlife is not a new phenomenon. The earliest civilizations were linked to the trade in live animals and parts thereof, from the Egyptian pharaohs to aristocrats in the modern era. This article focuses on the history of the wildlife trade in order to understand the social construction of the value of wildlife. In dynamic social and cultural contexts, the meaning of wildlife changes. Historically, exotic animals and the products thereof were associated with social elites, but today, wildlife attracts people from all walks of life and a wide variety of live animals and products thereof are traded for functional, symbolic and social purposes. Increasing ecocentric and biocentric values in contemporary western society, however, may influence constructed demand patterns for wildlife in the near future. By integrating cultural criminological concepts with the social construction of green crimes, this article aims to understand constructed wildlife consumerism through the ages.